1994
DOI: 10.1136/oem.51.1.35
|View full text |Cite
|
Sign up to set email alerts
|

Residual neurobehavioural effects associated with chronic exposure to mercury vapour.

Abstract: To find the residual effects of long term exposure to mercury vapour, neurobehavioural tests were given to ex-mercury miners about 18 years after the end of mercury exposure. Seventy six male exmercury miners who had been exposed to high concentrations of mercury vapour (over 1.0 mg/m3) and with a history of mercury intoxication were compared with controls matched for age (within 3 years), sex, and education. Although the extent of the workers' symptoms caused by mercury poisoning, termed erethismus merculiali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
45
0
7

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 16 publications
4
45
0
7
Order By: Relevance
“…The poorer performance on this test among the exposed workers is in accordance with the observation of impaired coordination in the clinical neurological examination of the same workers (24,25). Impaired manual dexterity or coordination has been suggested as an effect of past exposure to mercury vapors in other neuropsychological studies of previously exposed workers (26,27). Workers exposed to mercury vapors at the time of examination have been shown to have poorer results in similar tests (lo), whereas other studies on populations with lower exposure have shown no difference between exposed subjects and ref- erents (1 1, 17, 18).…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…The poorer performance on this test among the exposed workers is in accordance with the observation of impaired coordination in the clinical neurological examination of the same workers (24,25). Impaired manual dexterity or coordination has been suggested as an effect of past exposure to mercury vapors in other neuropsychological studies of previously exposed workers (26,27). Workers exposed to mercury vapors at the time of examination have been shown to have poorer results in similar tests (lo), whereas other studies on populations with lower exposure have shown no difference between exposed subjects and ref- erents (1 1, 17, 18).…”
Section: Discussionsupporting
confidence: 79%
“…This test did not discriminate between previously mercury-exposed lithium production workers and referents (27), and the test was not administered to previously exposed Japanese mercury miners (26). Soleo et a1 (12) did not observe poorer performance on this test in a small study on currently exposed workers who were compared with referents.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations